IMPROVING REPORT TEXT WRITINGTHROUGH THINK-PAIR-SHARE - Saliputra, Ade Dedi; Rufinus, Albert; Rosnija, Eni (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2013)
Abstrak:Penelitianinimerupakanpenelitianuntukmeningkatkankemampuansiswa SMA PGRI kelas X dalammenulisteks Report melaluimetodeberpasangan (Think Pair Share) tahunakademik 2012/2013. Tujuanpenelitianiniadalahuntukmengetahuibagaimanametode Think Pair Share digunakanuntukmeningkatkankemampuansiswadalammenulisteks report, denganharapanbahwapenelitianini bias bergunabagi guru dansiswadalam proses belajarmengajar.Metode yang digunakandalampenelitianiniadalahpenelitiantindakankelas yang terdiridariperencanaan, tindakan, observasidanrefleksi.Penelitimenggunakanduasiklusuntukmendapatkanhasil yang maksimal.Subjekpenelitianiniadalahsiswa SMA PGRI kelas X tahunakademik 2012/2013 yang berjumlah 30 siswa.Technique yang digunakanuntukmemperoleh data dalampenelitianiniadalahpengukurandanobservasilangsung.Alatpengumpulan data adalahtest tertulis, checklist, danlembarancatatan. Skor rata-rata siswapadasiklus 1 adalah 75,0dansiklus 2 adalah 79,16. Berdasarkan KKM (65) makaskor rata-rata jauhdiatasstandar, danpenelitiancukupdilakukandalamduasiklussaja. Kata kunci: meningkatkan, teks report, berpasangan, menulis. Abstract: The research is about improvingability on writing report text through Think-Pair-Share to the Tenth Grade Students of SMAPGRI I Pontianak in AcademicYear 2012/2013. The objective of the study is to know how the TPS improves the Students ability in writing report text. It is expected that the research would be useful for the teachers and students in language teaching and learning process. The method used in this research is a Classroom Action Research which consists of Planning, Acting, Observing and Reflecting. This method is done in two cycles in order to get the maximum result of the research.The subject of the study is the Tenth Grade Students of SMP PGRI I Pontianak in AcademicYear 2012/2013. The number of research participant is 30 students. The technique used for collecting data measurement technique and direct observation technique. The tools of collecting data arewritten test, observation checklist and field notes. In Cycle 1, the students mean score was 75.0. and cycle 2, the mean score was 79.16. Based on the minimum standard of pass (KKM), that is 65, the mean score of the first cycle was high and even more the second cycle. It means, the writer just does the research on two cycles. Keywords : Report, think pair share, writing.